Functions of Manduca sexta Hemolymph Proteinases HP6 and HP8 in Two Innate Immune Pathways - An, Chunju (American Society for Biochemistry and Molecular Biology, 2009)
Serine proteinases in insect plasma have been implicated in two types of immune responses; that is, activation of prophenoloxidase (proPO) and activation of cytokine-like proteins. We have identified more than 20 serine proteinases in hemolymph of the tobacco hornworm, Manduca sexta, but functions are known for only a few of them. We report here functions of two additional M. sexta proteinases, hemolymph proteinases 6 and 8 (HP6 and HP8). HP6 and HP8 are each composed of an amino-terminal clip domain and a carboxyl-terminal proteinase domain. HP6 is an apparent ortholog of Drosophila Persephone, whereas HP8 is most similar to Drosophila and Tenebrio spätzle-activating enzymes, all of which activate the Toll pathway. proHP6 and proHP8 are expressed constitutively in fat body and hemocytes and secreted into plasma, where they are activated by proteolytic cleavage in response to infection. To investigate activation and biological activity of HP6 and HP8, we purified recombinant proHP8, proHP6, and mutants of proHP6 in which the catalytic serine was replaced with alanine, and/or the activation site was changed to permit activation by bovine factor Xa. HP6 was found to activate proPO-activating proteinase (proPAP1) in vitro and induce proPO activation in plasma. HP6 was also determined to activate proHP8. Active HP6 or HP8 injected into larvae induced expression of antimicrobial peptides and proteins, including attacin, cecropin, gloverin, moricin, and lysozyme. Our results suggest that proHP6 becomes activated in response to microbial infection and participates in two immune pathways; activation of PAP1, which leads to proPO activation and melanin synthesis, and activation of HP8, which stimulates a Toll-like pathway.